“Invading Your Hearts and Minds”: Call of Duty® and the (Re)Writing of Militarism in U.S. Digital Games and Popular Culture - Frédérick Gagnon (European Journal of American Studies)
The goal of this article is to discuss how digital war games such as the Call of Duty series elicit consent for the U.S. military, militarism and the wars waged by the U.S. and its allies abroad. Building bridges between the humanities approach to Game Studies, American Studies, International Relations and Critical Geopolitics, we start from the assumption that digital games are more than “kid’s games”; they are sophisticated vehicles inhabiting and disseminating specific ideologies (Leonard 2004). Accordingly, our goal is to conduct a content analysis (Sisler 2008) of Call of Duty 4: Modern Warfare and Call of Duty: Modern Warfare 2 to show how these games contain images and narratives that (1) resonate with and reinforce a tabloid imaginary of post-9/11 geopolitics (Debrix 2008); (2) glorify military power and elicit consent for the idea that state violence and wars are inevitable; and (3) encourage our myopia by depicting a sanitized vision of war and downplaying the negative consequences of state violence (Stahl 2006). The conclusion invites players to think about ways to criticize the way games like Call of Duty employ and deploy values that (re)write the militarist mindset that has often pervaded the post-9/11 U.S. national security debate.